Resistensi Generasi Muda Terhadap Sistem Sosial Dalam Novel Kami Bukan Sarjana Kertas - Atika Ambarwati; Resdianto Permata Raharjo (Jurnal Ilmu Bahasa, Sastra, dan Budaya, 2026)
This study aims to analyze the forms of youth resistance toward the social system in the novel Kami (Bukan) Sarjana Kertas by J.S. Khairen through the representation of youth ideological values, the social background of the characters, social class inequality, and conflicts of interest between youth idealism and the established social system. This research is motivated by the increasing social pressures experienced by young people, particularly in the areas of education, economics, and socially constructed standards of success. This study employed a qualitative approach using a descriptive method. The theoretical framework applied was Alan Swingewood’s sociology of literature, which views literary works as reflections of social life. The data source of this research was the novel Kami (Bukan) Sarjana Kertas by J.S. Khairen. Data were collected through documentation techniques involving reading, identifying, recording, coding, and classifying quotations relevant to the research focus. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, conclusion drawing, and verification.The results of the study indicate that: (1) youth ideological values are represented through the spirit of striving for a better future, criticism of the education system, realistic attitudes toward life, parental expectations regarding education, and resistance to social and economic limitations; (2) the social background of the characters reflects the lives of lower-middle-class communities facing economic pressure, low self-confidence, and demands to achieve success through education; (3) social class inequality is portrayed through stigma toward students from non-prestigious universities, differences in family social status, unequal future opportunities, and the presence of social solidarity as a response to injustice; and (4) conflicts of interest emerge through tensions between youth idealism and a social system that continues to prioritize academic formality and educational status. This study concludes that the novel Kami (Bukan) Sarjana Kertas functions as a medium of social criticism toward the education system and social inequality that still exist in society.